The Effect Of Work Ability, Workload, And Skills On The Performance Of North Bengkulu Police Personnel (The Manager Review, 2024)
This study aims to analyze the effect of work ability, workload and skills on the performance of North Bengkulu Police personnel. This type of research uses quantitative descriptive approach research with survey method. In this study, the authors collected information data and basic information using a questionnaire distributed to the North Bengkulu Police Personnel as many as 264 people. The data analysis method used descriptive analysis and multiple regression analysis. The results showed that: (1) Adequate work ability is proven to be an important factor that encourages the improvement of the performance of Polri personnel. The higher the work ability of personnel, the better the resulting performance; (2) Workload in accordance with individual capacity also has a positive influence on the performance of Polri personnel. Excessive workload can reduce performance, while a balanced workload can improve performance; (3) Adequate work skills, including technical, conceptual, and interpersonal skills, have been shown to contribute significantly to improving the performance of Polri personnel and (4) Overall, the three factors (work ability, workload, and work skills) play an important role in determining the performance of Polri personnel and need to be managed properly to achieve optimal performance. This means that if the work ability is higher, the workload is more balanced and the work skills are better, the personal performance of North Bengkulu Police will also be higher.